Rancang Bangun Sistem Informasi Cyber Campus (SICyCa) Berbasis Mobile Android pada Institut Bisnis dan Informatika Stikom Surabaya - Wicaksono, Andhika Maheva; Sutanto, Teguh; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
In 2013 Institut Bisnis dan Informatika Stikom Surabaya through Pengembangan dan Penerapan Teknologi Informasi (PPTI) released SICyCa Mobile. On the implementation, SICyCa Mobile experience some errors which the data shown in the application does not match with the existing data in the database. So the informations related to the daily schedule, KRS, and college histories which contained in the application is not valid. Besides this, there are some problems in the use of SICyCa this time where the SICyCa is more passive, so some academic informations can’t be conveyed to students who are didn’t use SICyCa or open SICyCa directly. To solve these problems, the solution is developed an Android application called SICyCa Mobile. SICyCa Mobile has push notification to help students get latest information with Android device. From test results, SICyCa Mobile can run properly and match with the user needs and specifications have been determined, in Addition the notification and reminder features can be used in accordance with its function.